Optische Konstanten von Substraten im NIR/MIR‐Spektralbereich: Bestimmung mittels Fourier‐Transform‐Infrarot‐(FTIR‐)Spektrometrie. (February 2016) - Franke, Christian; Stenzel, Olaf; Wilbrandt, Steffen; Schürmann, Mark; Wolf, Josephine; Todorova, Vera; Doherty, Brenda; Kaiser, Norbert
Abstract : Determination of the Optical Constants of Common Substrate Materials in the NIR/MIR‐Spectral Regions An approach is reported for determining the optical constants of substrates and single layer coatings in the near and mid‐infrared spectral regions. A combination of the algorithm from Nichelatti and a multi‐oscillator model has been used to determine the optical constants of the substrates. Thus, the approach even works when the sample transmittance is vanishing. We demonstrate the application of the approach to the evaluation of transmission and reflection spectra of common substrates (CaF2, Q1, Sapphire) measured by a Fourier‐Transform‐Infrared spectrophotometer. The comparison of the calculated optical constants with values reported in literature confirms the validity of the used approach. We also demonstrate the IR characterisation of a tantalum oxide single layer deposited onto a Q1 substrate by means of the multi‐oscillator‐model. The results are again in good agreement with literature data.